2021
DOI: 10.3389/fmars.2021.720413
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity and Nitrogen Metabolism of Culturable Nitrate-Utilizing Bacteria Within the Oxygen Minimum Zone of the Changjiang (Yangtze River) Estuary

Abstract: The nitrogen cycle is an indispensable part of the biogeochemical cycle, and the reactions that occur in the ocean oxygen minimum zone (OMZ) mediate much of the loss of nitrogen from oceans worldwide. Here, nitrate-utilizing bacteria were isolated from the water column at 17 stations within the OMZ of the Changjiang (Yangtze River) Estuary using selective media and a culture-dependent method. The microbial diversity, nitrogen metabolism and nitrate reduction test of culturable heterotrophic bacteria were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…The significant influence of soil atom % 15 N on dominant soil bacteria in our study suggests that the application of fertilizer has the potential to regulate soil bacterial composition on the phylum level by changing the N content in soils. The positive correlations between Proteobacteria taxa and soil NH 4 + suggest that soil NH 4 + is the preferred inorganic N form for these selected bacterial phyla [55][56][57]. The negative correlations between Proteobacteria taxa and soil TN agree with other reports [2,58].…”
Section: Influence Of Biochar and Fertilizer On Relationships Between...supporting
confidence: 88%
“…The significant influence of soil atom % 15 N on dominant soil bacteria in our study suggests that the application of fertilizer has the potential to regulate soil bacterial composition on the phylum level by changing the N content in soils. The positive correlations between Proteobacteria taxa and soil NH 4 + suggest that soil NH 4 + is the preferred inorganic N form for these selected bacterial phyla [55][56][57]. The negative correlations between Proteobacteria taxa and soil TN agree with other reports [2,58].…”
Section: Influence Of Biochar and Fertilizer On Relationships Between...supporting
confidence: 88%
“…Another study reported that M. nauticus isolated from water of an oil field in Vietnam was able to grow in wide ranges of temperatures (13°C–50°C) and salinity (0–20% NaCl) (Huu et al, 1999), therefore consider as a halotolerant bacterium (Tourova et al, 2022). Additionally, M. nauticus have been documented to carry genes involved in denitrification pathways ( nirS , norBC , and nosZ ) in which nitrate is reduced to molecular nitrogens (He et al, 2021; Jiang et al, 2023). However, no study, to the authors' knowledge, has reported specifically that M. nauticus is able to degrade ammonia; therefore the present study is the first study to report the capacity of M. nauticus to degrade ammonia.…”
Section: Discussionmentioning
confidence: 99%